The impact of the financial crisis on human resources for health policies in three southern-Europe countries - Correia, T. (2016)
The public health sector has been the target of austerity measures since the global financial crisis started in 2008, while health workforce costs have been a source of rapid savings in most European Union countries. This article aims to explore how health workforce policies have evolved in three southern European countries under external constraints imposed by emergency financial programmes agreed with the International Monetary Fund, Central European Bank and European Commission. The selected countries, Greece, Portugal and Cyprus, show similarities with regard to corporatist systems of social protection and comprehensive welfare mechanisms only recently institutionalized. Based on document analysis of the Memoranda of Understanding agreed with the Troika, our results reveal broadly similar policy responses to the crisis but also important differences. In Cyprus, General Practitioners have a key position in reducing public expenditure through gatekeeping and control of users' access, while Portugal and Greece seeks to achieve cost containment by constraining the decision-making powers of professionals. All three countries lack innovation as well as monitoring and assessment of the effects of the financial crisis in relation to the health workforce. Consequently, there is a need for health policy development to use human resources more efficiently in healthcare